Effect of Amphiphiles on Hypertonic Hemolysis of Erythrocytes, Modified with Temperature of 49°C - Pisarenko, N. A.; Shpakova, N. M. (Problems of Cryobiology and Cryomedicine, 2011)
The effect of thermal pre-treatment of human and bovine erythrocytes on their sensitivity to hypertonic stress (4.0 mol/l NaCl) at 37 and0°Cwas studied. It has been shown that cell incubation at49°C, causing spectrin denaturation, decreases the level of human erythrocyte hypertonic damage and does not affect the integrity of bovine erythrocytes at37°C. Hypertonic hemolysis of modified mammalian erythrocytes does not change at0°C. Cytoskeletal spectrin denaturation of bovine and human erythrocytes results in reduction of antihemolytic activity of amphiphilic substances (sodium decyl sulfate, dodecyl-β,D-maltoside, trifluoroperazine) at 37 and0°C.